An immunogenic cell death-associated classification predictions are important for breast invasive carcinoma prognosis and immunotherapy - Liao, Xinghe; Liu, Hui; Zhang, Zhe; Zhang, Jing; Zhang, Chenyue; Zhao, Weiwei (Frontiers in Genetics, 2022)
A type of regulated cell death (RCD), immunogenic cell death (ICD) can initiate the adaptive immune response. Numerous reports highlight the possibility that ICD alters the tumor immune microenvironment by releasing DAMPs, or danger signals, which could support immunotherapy. The discovery of the ICD-linked biomarkers is crucial at the moment. In this report, the consensus clustering technique was used to identify two subcategories (subtypes) linked to ICD. In comparison to the ICD-low subcategory, the ICD-high subcategory showed a longer survival period and more immune cell infiltration. Then, a novel ICD-associated prognostic model was developed and validated for predicting the survival of patients with breast invasive carcinomas (BRCA) and is linked to the tumor immune microenvironment. To conclude, a novel ICD-based BRCA classification scheme was designed. For individuals with BRCA, this categorization will be crucial for directing the assessment of prognosis and treatment.